BULLYING PREVENTION STRATEGY THROUGH IMPLEMENTATION OF P5 PROJECT IN ELEMENTARY SCHOOL ENVIRONMENT - Yeni Ratna Hidayah; Ndaru Mukti Oktaviani; Wida Wardatu Sofa; Yusri Nidaus Salam; Wanda Meliyana Putri (UPT. PKM UB, 2025)
Bullying in elementary schools is a serious problem that impacts the physical, emotional, and social well-being of students. This community service activity aims to prevent bullying through the implementation of the Pancasila Student Profile Strengthening Project at SDN 4 Awirarangan with the theme Build Your Soul and Body: Together Create a Comfort Zone, Free from Bullying. The program is designed using the Merdeka flow approach which involves a series of reflective, educational, collaborative, and real action activities such as filling out reflective questionnaires, discussions with resource persons, visual campaigns through posters, and anti-bullying declarations. The results of the activity showed active participation of students in recognizing their roles as perpetrators, victims, or witnesses of bullying as well as increasing awareness and empathy for the importance of creating a safe and inclusive learning environment. This school-based approach has proven effective in building an anti-bullying culture from an early age, as well as strengthening students' commitment as agents of social change in the school environment.